Evaluation of Methylene Blue as An Effective Antiseptic for Medicinal Leeches (Hirudo verbana) - Doğan, Sibel; Farzali, Shabnam; Karimova, Boyukkhanım; Sağlam, Naim (Galenos Publishing House, 2024)
Objective: Medicinal leeches (Hirudo spp.) have been used for therapeutic purposes in humans since ancient times. Because of their growth conditions, leeches carry certain bacteria and endosymbionts (e.g., Aeromonas spp). In both leech farms and hirudotherapy clinics, there are no reliable antiseptics that can be used with leeches. This study aimed to determine whether methylene blue (MB) is a safe antiseptic for medicinal leeches and assess its safe usage. Methods: This study evaluated the efficacy of MB by determining lethal concentrations (LC), effective concentrations (EC), and lethal times (LT) for the medicinal leech Hirudo verbena Carena, 1820. A total of 570 H. verbana specimens obtained from a local farm were used in this study. Eighteen different concentrations of MB (between 1 ppm and 512 ppm) were tested. Results: The LC50 and EC50 values for H. verbana were determined to be 60.381 (53.674-66.636) ppm and 2.013 (1.789-2.221) ppm, respectively. The LT50 durations for MB concentrations of 32 and 512 ppm were calculated as 212.92 h (138.43 h-1485.78 h) and 17.82 h (8.08 h-23.90 h), respectively. Conclusion: The results show that MB concentrations between 2 and 19 ppm can be safely used as antiseptics in hirudotherapy clinics and leech farms to address bacterial concerns caused by medicinal leeches. © 2024 Turkish Society for Parasitology-Available online at www.turkiyeparazitolderg.org.
Metilen Mavisinin Tıbbi Sülükler (Hirudo verbana) için Etkili Bir Antiseptik Olarak Değerlendirilmesi
Keywords: antiseptics; hirudotherapy; lethal concentrations; lethal times; Medicinal leech; methylene blue